Chromatographic profiling of leniolisib impurities using HPLC and LC-MS/MS: degradation behaviour, structural characterization, and in-silico toxicity evaluation - Gunupati, Rahul; Tulasi, S. Lakshmi; Shaik, Rasheed Babu; Lakshmi, L. Bhagya; Tangeti, Venkata Swamy (Creative Pharma Assent, 2025)
Background: This study presents a comprehensive analytical investigation of leniolisib, focusing on impurity profiling, degradation kinetics, structural characterization, and in silico toxicity prediction of degradation products (DPs). Methodology: A systematic approach was employed to optimize the analytical method for leniolisib and its impurities, along with LC–MS/MS-based identification and in-silico toxicity prediction of DPs. Result and Discussion: Method optimized as Waters Symmetry C18 column and an isocratic mobile phase (methanol: sodium acetate buffer, 55:45 v/v) at 0.90 mL/min with UV detection at 229 nm. Leniolisib was most susceptible to acid and oxidative stress, resulting in 31.24% and 39.58% degradation, respectively. Pseudo-first-order kinetics was observed with rate constants of 0.0329 h⁻¹ (acidic) and 0.0414 h⁻¹ (oxidative), with half life of 21.08 h and 16.73 h. LC–MS/MS elucidates the identities of major DPs that enable the proposed degradation pathways. The MS/MS characterization confirms DP 1 with a formula of C13H15N5O with a mass of 257 g/mol, whereas DP 2, 3, and 4 were identified to have formulas of C20H26N6O2, C13H12F3N5O, and C17H19F3N6O with masses of 382, 311, and 380 g/mol, respectively. The In-silico toxicity predictions show DP 1 (LD₅₀ = 500 mg/kg) and DP 2 (729 mg/kg) as moderate toxicity (class 4), DP 4 shows the least toxicity (class 5, LD₅₀ = 1750 mg/kg), whereas DP3 shows the highest toxicity (class 3, LD₅₀ = 250 mg/kg). Conclusion: The developed method and accompanying data provide a critical foundation for routine quality control, stability testing, and regulatory submissions for leniolisib-based formulations.